Synthesis and Applications of tert-Alkylphosphines - Barber, Thomas (2021)
tert-Alkyl-substituted phosphines are commonly used as ligands in metal catalysis due to their sterically bulky, electron-rich nature. Methods to synthesise them by P–C bond formation are inefficient and operationally complex, requiring highly reactive organometallic reagents and chlorophosphines (Chapter 1). Despite advances in varying other groups on phosphorus to improve catalytic performance, the diversity of tert-alkyl groups remains low.